The Impact of Education on Patriarch Culture and Gender Equality - Benedikta Yosefina Kebingin; Armada Riyanto (P3TK, Sanata Dharma University, 2022)
This article will explore the independence that is actually expected by every human being, both women and men in the framework of education under the title,